2021
DOI: 10.1002/ppul.25533
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of age at diagnosis and clinical findings of children with primary ciliary dyskinesia

Abstract: Objective: Patients with primary ciliary dyskinesia (PCD) may present with different clinical findings at different ages, and age at diagnosis may differ. We aimed to review clinical factors that affected age at diagnosis of patients with PCD.Study Design: All 70 patients with PCD who were followed in our pediatric pulmonology department were included. Demographic features, clinical findings, PrImary CiliAry DyskinesiA Rule (PICADAR) scores and pulmonary function tests of patients were recorded and clinical fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…This younger age at diagnosis for those with situs abnormalities may be attributed to higher clinical suspicion and earlier presentation, and this is consistent with the results in two prior studies. 30,31 Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran. [32][33][34] ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort.…”
Section: Discussioncontrasting
confidence: 96%
“…This younger age at diagnosis for those with situs abnormalities may be attributed to higher clinical suspicion and earlier presentation, and this is consistent with the results in two prior studies. 30,31 Regarding TEM findings, in contrast to the current study that showed ODA loss and MTD + IDA loss to be equally the most common hallmark defects, ODA + IDA loss was the most common hallmark defect reported in previous studies in the Kingdom of Saudi Arabia (KSA), Oman, and Iran. [32][33][34] ODA absence as a Class 1 hallmark defect was not reported among the Iranian cohort.…”
Section: Discussioncontrasting
confidence: 96%
“…Patients with scores of ≥5 should be evaluated for PCD. 6 The patient presented in this case report had a PICADAR score of 6. The relatively low PICADAR score might be another factor that delayed the PCD diagnosis.…”
mentioning
confidence: 78%
“…The maximum score obtained using PICADAR is 14. Patients with scores of ≥5 should be evaluated for PCD 6 . The patient presented in this case report had a PICADAR score of 6.…”
Section: Parameter (Normal Value)mentioning
confidence: 97%
“…In another multicenter study conducted in England, the mean age at diagnosis was 2.6 years 28 . In a recent study in Turkey, it was found to be 8.3 years 29 . Children are usually diagnosed with CF in the first months of life with the implementation of CF newborn screening in many countries 30 .…”
Section: Discussionmentioning
confidence: 99%
“…28 In a recent study in Turkey, it was found to be 8.3 years. 29 Children are usually diagnosed with CF in the first months of life with the implementation of CF newborn screening in many countries. 30 In our study, the age at diagnosis of children with PCD was significantly older than children with CF.…”
Section: T a B L E 1 Sociodemographic Features And Clinical Character...mentioning
confidence: 99%